Cardiovascular disease risk factors in the Lubelskie Voivodeship in 2008-2018 - part II: the obesity epidemic - Jankowski, Krzysztof (Kwartalnik Naukowy Fides et Ratio, 2022)
Introduction: All over the world, the problem of excess body weight is being raised more and more frequently. In 2021. the number of obese people has tripled compared to 1975. Due to the constantly growing number of people meeting the criteria for overweight and obesity, it is becoming extremely important to implement preventive measures. Cardiovascular Diseases Prevention Program implemented in Poland as part of the National Health Fund program is a good opportunity to identify patients with abnormal body weight and to correct behavior and health education. Material: A retrospective analysis of data obtained by the National Health Fund as part of the implementation of 86,485 preventive cards of the Cardiovascular Diseases Prevention Program in the Lubelskie Voivodeship in 2008-2018 was carried out. The analyzes were performed using the IBM SPSS Statistics for Windows, version 25 program. The chi-square test and the Pearson linear correlation between the quantitative features were used to test the relationship between the two qualitative features. Significant predictors of a risk factor for cardiovascular disease were determined using multivariate logistic regression. The significance level was assumed to be α = 0.05 for two-tailed tests. Results: The average BMI value was 26.12 kg / m2. 1st degree obesity was diagnosed in 14.3% of patients, 2nd degree - 2.9%, 3rd degree - 0.7%. Excess body weight was significantly more often observed among men. With the increase in the number of years in the study population, the occurrence of overweight and obesity was significantly higher. One unit increase in BMI was associated with a 13% increase in the risk of high blood pressure and a 12% increase in the risk of serum glucose ≥126 mg/dl. It also increased the risk of hypercholesterolaemia by 4.2% and of elevated LDL levels by 5.5%. Conclusions: The prevalence of obesity is extremely worrying. Excessive body weight undeniably translates into worse health of the population. The Cardiovascular Diseases Prevention Program at Primary Healthcare Clinics is a convenient opportunity to identify the factors leading to the development of obesity and to promote health-promoting behaviors.